Evaluation on Security of Water Resources in Shiyan City Based on Water Poverty Index - JIANG Huining; YAN Baowei; HUO Lei; CAO Chen (Renmin Zhujiang)
Based on the basic concepts and calculation principles of water poverty index (WPI), thispaper takes the Shiyan City in the upper reaches of the Hanjiang River as the research object,selects 23 indicators from the aspects of resources, environment, society and economy, etc.,determines the evaluation weights of each index by the entropy method, and builds the scientific andrational water resources security evaluation system to conduct a comprehensive and systemicevaluation for the security of water resources in Shiyan City. The results suggest that the waterresources security of Shiyan City generally presents a trend of increase, but there are still weaklinks such as poor water supply facilities. Finally, some suggestions for dealing with local waterresources security issues are put forward according to the new idea of “overcoming weakness inwater conservancy project and strengthening supervision on water conservancy industry”. The researchresults can provide a useful reference for the security warning of water resources in Shiyan City.